1980
DOI: 10.1161/01.res.47.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal and hepatic venous congestion on renal function in the presence of low and normal cardiac output in dogs.

Abstract: We investigated the effect of acute renal vein and hepatic vein hypertension induced by partial balloon-occlusion of the abdominal inferior vena cava (AIVC-O) and the thoracic inferior vena cava (TIVC-O) on systemic and renal hemodynamics and renal function in 13 dogs anesthetized with pentobarbital. When a renal vein pressure of 13 cm H2O was induced by AIVC-O, cardiac output, stroke volume, central venous pressure, renal blood flow, and renal function (GFR, free water clearance, osmolar clearance, urine outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Studies in animals have shown that increasing renal venous pressure leads to a reduction in glomerular filtration, which was probably mediated by a decreased renal perfusion (19). Renal vein constriction led to a decrease in GFR in rats (20), whereas renal function decreased when renal vein pressure was increased in dogs, but only when cardiac output was reduced (21). We recently showed that in patients with reduced cardiac function, secondary to pulmonary hypertension, increased CVP was strongly associated with renal impairment, especially when renal perfusion was already impaired (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals have shown that increasing renal venous pressure leads to a reduction in glomerular filtration, which was probably mediated by a decreased renal perfusion (19). Renal vein constriction led to a decrease in GFR in rats (20), whereas renal function decreased when renal vein pressure was increased in dogs, but only when cardiac output was reduced (21). We recently showed that in patients with reduced cardiac function, secondary to pulmonary hypertension, increased CVP was strongly associated with renal impairment, especially when renal perfusion was already impaired (11).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the isolated perfused rat kidney model, GFR was not significantly altered until the imposed venous pressure reached 25 mmHg . In a dog model of renal vein hypertension, renal dysfunction occurred only when CO was concomitantly reduced . Notwithstanding, it is possible that the kidneys are more sensitive to elevated CVP in the setting of heart failure, such that GFR may fall with moderate CVP elevations …”
Section: Discussionmentioning
confidence: 99%
“…Sodium and water retention ultimately lead to volume overload, which is strongly linked to increased filling pressures, including right‐sided pressures . The resulting elevation of venous pressure is one of the most common manifestations of congestion in heart failure, and may adversely affect the kidneys …”
Section: Introductionmentioning
confidence: 99%
“…In an animal model of renal venous hypertension, GFR only declined when cardiac output was concomitantly impaired. 46 Similarly, recent clinical studies reported that CVP was an independent predictor of WRF, but especially when there was low cardiac output. 11,44 These apparently conflicting results may reflect the multifactorial nature of this interaction.…”
Section: Fluid Overload-renal Venous Congestionmentioning
confidence: 94%